PENGUKURAN TINGKAT KAPABILITAS APLIKASI MOBILISASI AVIATION SECURITY DENGAN MENGGUNAKAN FRAMEWORK COBIT 5 PADA DOMAIN EDM, APO, DSS (STUDI KASUS: PT ANGKASA PURA II) - Nurhadi Malvin Prayoga (2020)
Aviation Security at Soekarno-Hatta Airport has many personnel and security areas. Therefore we need a tool to be able to monitor the entire movement of Aviation Security personnel and optimize the number of existing personnel. The tools used today are Aviation Security mobilization applications that are useful for facilitating Aviation Security personnel in reporting, checking tools used, managing available personnel, reporting related to Accident and Incident and also rotating and mobilizing personnel. So the purpose of this study is to analyze the measurement of mobilization applications in the scope of Aviation Security. In this study the authors use the COBIT 5 framework with EDM (Evaluate, Direct, Monitoring), APO (Align, Plan, and Organize) and DSS (Deliver, Service, Support) domains. The output to be achieved in this research is a conclusion measuring the capability level of the Aviation Security mobilization application as a benchmark / reference in managing the information system. In this study the capability level of mobilization applications in Aviation Security is at level 2 (the process has been implemented with certain management (planned, monitored, adjusted) and the results can be determined, controlled, and maintained appropriately).